Development of Gamification-Based HTML5 Interactive Learning Media for Human Digestive System in Elementary Education - Sarira, Maria Jayanti; Sabariah, Sabariah; Suharti, Suharti (Universitas Pendidikan Mandalika, 2025)
This study aims to develop interactive learning media based on HTML5 with a gamification approach to improve students' understanding, activeness, and learning motivation. This research used a Research and Development (R&D) method with the ADDIE model, consisting of five main stages: analysis, design, development, implementation, and evaluation. The validation process was carried out by three experts using a feasibility assessment instrument, followed by a limited trial with fifth-grade students at SD Negeri Inpres Malompo Elementary School. Data analysis was conducted quantitatively through validation questionnaires and student responses. The findings indicated that the media was considered